Mass-Spectrometry-Based Research of Cosmetic Ingredients - Alina Florina Serb; Marius Georgescu; Robert Onulov; Cristina Ramona Novaconi; Eugen Sisu; Alexandru Bolocan; Raluca Elena Sandu (Molecules, 2024)
Cosmetic products are chemical substances or mixtures used on the skin, hair, nails, teeth, and the mucous membranes of the oral cavity, whose use is intended to clean, protect, correct body odor, perfume, keep in good condition, or change appearance. The analysis of cosmetic ingredients is often challenging because of their huge complexity and their adulteration. Among various analytical tools, mass spectrometry (MS) has been largely used for compound detection, ingredient screening, quality control, detection of product authenticity, and health risk evaluation. This work is focused on the MS applications in detecting and quantification of some common cosmetic ingredients, i.e., preservatives, dyes, heavy metals, allergens, and bioconjugates in various matrices (leave-on or rinse-off cosmetic products). As a global view, MS-based analysis of bioconjugates is a narrow field, and LC- and GC/GC×GC-MS are widely used for the investigation of preservatives, dyes, and fragrances, while inductively coupled plasma (ICP)-MS is ideal for comprehensive analysis of heavy metals. Ambient ionization approaches and advanced separation methods (i.e., convergence chromatography (UPC2)) coupled to MS have been proven to be an excellent choice for the analysis of scented allergens. At the same time, the current paper explores the challenges of MS-based analysis for cosmetic safety studies.